Building Students' Ecological Awareness: Integrative Design of the Islamic Education Curriculum - Resky, Muhammad (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The world is facing a severe ecological crisis, evidenced by record-high global temperatures and significant environmental degradation in Indonesia, such as deforestation, poor air quality, and the threat of sinking islands. The purpose is to foster deep ecological awareness in students by integrating ecological, psychological, and sociological theories into the existing PAI framework. This study utilizes a qualitative method with a descriptive-analytical approach, specifically a literature concept analysis. Data was sourced from academic articles, books, and journals focusing on ecological theories (Bronfenbrenner), psychological theories (Theory of Planned Behaviour), and sociological theories (Ibn Khaldun) in the context of Islamic education and environmentalism. The research produces a comprehensive, integrative PAI curriculum model. This model systematically embeds ecological, psychological, and sociological concepts into the five core PAI subjects: Qur'an-Hadith, Aqidah, Akhlak, Fiqh, and History of Islamic Culture. The model redefines the teacher's role as a facilitator and collaborator, emphasizes contextual learning methods like Project-Based and Problem-Based Learning, and outlines an authentic evaluation system to assess cognitive, affective, and psychomotor domains related to environmentalism. The proposed curriculum model offers a transformative approach to PAI, making it relevant to contemporary environmental challenges. Its implementation can cultivate a generation of students who possess not only ritual piety but also strong social and ecological piety, empowering them to become agents of change for environmental sustainability as a true embodiment of rahmatan lil 'alamin (mercy for all worlds).